1996
DOI: 10.1152/ajpheart.1996.271.5.h2007
|View full text |Cite
|
Sign up to set email alerts
|

Control of arteriovenous anastomoses in rabbit ear model of digital perfusion

Abstract: The arteriovenous anastomoses (AVA) of the cutaneous microcirculation of the hands and feet are fundamental determinants of thermoregulatory blood flow and may be involved in cold intolerance. These direct microvascular studies are an initial characterization of adrenergic receptor subtypes participating in control of AVA in the ears of anesthetized male New Zealand White rabbits. Adrenergic alpha 1-stimulation with phenylephrine produced AVA constriction, whereas terazosin (an alpha 1-antagonist) produced dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The present study revealed that phenylephrine induced significant vasoconstriction among arterioles, arteriovenous anastomoses, and venules. The arteriovenous anastomoses were identified as the part of the ear microvasculature most sensitive to extramural aIadrenoceptor stimulation: this is in agreement with prcvious studies (9,16). In arterioles, a significanl rightward shift of the phenylephrine concentrationresponse curve was noted in the ear vasculature treatcd with 5-methyl-urapidil or BMY7378.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The present study revealed that phenylephrine induced significant vasoconstriction among arterioles, arteriovenous anastomoses, and venules. The arteriovenous anastomoses were identified as the part of the ear microvasculature most sensitive to extramural aIadrenoceptor stimulation: this is in agreement with prcvious studies (9,16). In arterioles, a significanl rightward shift of the phenylephrine concentrationresponse curve was noted in the ear vasculature treatcd with 5-methyl-urapidil or BMY7378.…”
Section: Discussionsupporting
confidence: 88%
“…This experiment utilized an acute in vivo preparation of the microvasculature of the rabbit ear as previously described (16). Experimental protocols were approved by the Animal Care and Use Committee of the University and followed the National Institutes of Health guidelines for the care and use of laboratory animals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following a cold thermal stress, the auricular circulation in normal rabbits is characterized by an overall reduction in blood flow in the ear and cutancous perfusion similar to that observed in human digits (22). Recent in vivo studies of the rabbit have identified specific receptor innervation of the ear microvasculature, with a,-adrenoceptor control predominating over arteriovenous anastomosis regulation (18). Therefore, it was hypothesized that in the rabbit car, cold exposure would decrcase the arteriovenous-shunt flow to a greater cxtent than nutritional flow by enhancing the microvascular a2-adrenoceptor response to norepinephrine.…”
mentioning
confidence: 83%